Nucleotide polymorphism-based study utilizes human plasma liposomes to discover potential therapeutic targets for intervertebral disc disease - Chen, Ding-Qiang; Que, Zhi-Qiang; Xu, Wen-Bin; Xiao, Ke-Yi; Sun, Nai-Kun; Song, Hong-Yu; Feng, Jin-Yi; Lin, Guang-Xun; Rui, Gang (Frontiers in Endocrinology, 2024)
While intervertebral disc degeneration (IVDD) is crucial in numerous spinally related illnesses and is common among the elderly, the complete understanding of its pathogenic mechanisms is still an area of ongoing study. In recent years, it has revealed that liposomes are crucial in the initiation and progression of IVDD. However, their intrinsic mediators and related mechanisms remain unclear. With the development of genomics, an increasing amount of data points to the contribution of genetics in the etiology of disease. Accordingly, this study explored the causality between liposomes and IVDD by Mendelian randomization (MR) analysis and deeply investigated the intermediary roles of undetected metabolites. According to MR analysis, 179 liposomes and 1400 metabolites were evaluated for their causal association with IVDD. Single nucleotide polymorphisms (SNPs) are strongly associated with the concentrations of liposomes and metabolites. Consequently, they were employed as instrumental variables (IVs) to deduce if they constituted risk elements or protective elements for IVDD. Furthermore, mediation analysis was conducted to pinpoint possible metabolic mediators that link liposomes to IVDD. The inverse variance weighting (IVW) was the main analytical technique. Various confidence tests in the causality estimates were performed, including consistency, heterogeneity, pleiotropy, and sensitivity analyses. Inverse MR analysis was also utilized to estimate potential reverse causality. MR analysis identified 13 liposomes and 79 metabolites markedly relevant to IVDD. Moreover, the mediation analysis was carried out by choosing the liposome, specifically the triacylglycerol (48:2) levels, which were found to be most notably associated with an increased risk of IVDD. In all, three metabolite-associated mediators were identified (3-methylcytidine levels, inosine 5'-monophosphate (IMP) to phosphate ratio, and adenosine 5'-diphosphate (ADP) to glycine ratio). The analysis's findings suggested possible causal connections between liposomes, metabolites, and IVDD, which could act as both forecast and prognosis clinical indicators, thereby aiding in the exploration of the pathogenesis behind IVDD.